Effects of different salinities and pH on the growth and proximate composition of Nannochloropsis sp. and Tetraselmis sp. isolated from South China Sea cultured under control and natural condition - Azizah, Endut; Helena, Khatoon; Norazira, Abdu Rahman (2014)
Nannochloropsis sp. and Tetraselmis sp. are widely used in aquaculture as a source of protein, lipid and carbohydrate. The growth and proximate composition of microalgae could be affected by different culture conditions especially salinity, temperature and light. Thus, this study was aimed to compare the growth and proximate composition of Nannochloropsis sp. and Tetraselmis sp. cultured in different salinities and pH under different culture conditions. In this study Nannochloropsis sp. and Tetraselmis sp. were isolated from South China Sea and cultured at different salinities of 20, 30 and 40 ppt and different pH of 5.5, 7.5, 8.5 and 9.5 under natural and control condition until stationary phase. Results showed that Nannochloropsis sp. and Tetraselmis sp. had signiﬁcantly higher (p<0.05) cell density, lipid and carbo-hydrate content under control condition at 30 ppt. However, protein content was signiﬁcantly higher(p<0.05) in Nannochloropsis sp. when cultured under natural condition at 30 ppt. High cell density, protein, lipid and carbohydrate content was obtained when cultured at pH 7.5 and 8.5 for both species. The output of this study could be considered for Nannochloropsis sp. and Tetraselmis sp. cultivation to provide appropriate levels of protein, lipid and carbohydrate as feed supplement for aquaculture organisms.